Testes de vigor para avaliação do portencial fisiológico de sementes de abóbora(Cucurbita moschata Duch.) - Calheiros, Verônica Schinagl (2010)
The need for obtaining reliable results in a relatively short period of time, to evaluate the physiological quality of seeds, has increased the interest in the use of vigor tests more sensitive for lots selection, supplementing the information of the germination test. The aim of this study was to evaluate the efficiency of different tests to determine the physiological potential of pumpkin seeds. It was used five batches of pumpkin seeds, Menina Brasileira Precoce cultivar. It was performed evaluations of water content, germination, germination speed index, emergence speed index, emergence in greenhouse and field, length and dry phytomass of aerial part, root and total of seedling. It was conducted the accelerated aging test in the respective methodologies: traditional - water (RH = 100%), saturated saline solution - 40g NaCl/100ml (RH = 76%) and non saturated saline solution - 11g NaCl/100ml (RH = 88 %) at 41°C, for periods of 48 and 72 hours. And the controlled deterioration test, with adjustment of seeds water content to 25% at 41°C, for 24 and 48hours. The trial was conducted in a randomized design with four replications. The trial was conducted in a randomized design, the averages for each lot in each assessment were compared with Tukey test, at probability level of 5% and were compared by linear correlation test. It was noted that controlled deterioration tests for 48hs and accelerated aging using non saturated saline solution for 48hs are efficient to evaluate the physiological potential of pumpkin seed lots.